Fungsi Sosial Kegiatan Mentoring Keagamaan di BSO Masjid Al-Ijtima’i dalam Pembinaan Mahasiswa: Analisis Perspektif Talcott Parsons - Nayla Nur Rahmawati; Muhamad Ridwan Effendi (Advances In Education Journal, 2025)
This study examines the Religious Mentoring program at the Semi-Autonomous Body (BSO) of Al-Ijtima’i Mosque as a form of religious development for university students. The study aims to describe the implementation of mentoring, explain its goals and orientation, and analyze its social functions in students’ campus life. This research uses a qualitative approach, with data collected through in-depth interviews, participant observation, and documentation involving mentors and mentees. The findings show that mentoring is conducted in small groups through regular and flexible meetings. The program not only focuses on improving religious practices and understanding, but also provides emotional support, strengthens social bonds, and encourages students’ social engagement. Using Talcott Parsons’ AGIL framework, mentoring is understood as a social system that adapts to students’ conditions, directs developmental goals, fosters group integration, and maintains religious values. These findings indicate that mentoring plays an important role in supporting students’ religious identity and social stability within the dynamic campus environment.